Individual differences in oral tactile sensitivity and gustatory fatty acid sensitivity and their relationship with fungiform papillae density, mouth behaviour and texture perception of a food model varying in fat. (June 2021) - Zhou, Xirui; Yeomans, Martin; Thomas, Anna; Wilde, Peter; Linter, Bruce; Methven, Lisa
Highlights: Individuals differ in papillae density, oral tactile and fat taste sensitivity. Fungiform papillae density positively correlates with oral tactile sensitivity. Higher fungiform papillae density related to higher fat taste sensitivity. Fungiform papillae density and tactile sensitivity influence mouthfeel perception. BMI related to oral tactile sensitivity and perception of greasy. Abstract: Fat provides multimodal stimulation, particularly through mouthfeel and as a taste stimulant via free fatty acids. Individuals vary in perception of both mouthfeel and taste sensations from fat. Papillae number on the tongue can influence oral tactile and taste sensitivity. In addition, mouth behaviour (how foods are manipulated in the mouth during eating before swallowing) varies between individuals, and may influence mouthfeel perception. Limited research has explored the relationships between these factors. Fatty acid (FA) taste sensitivity was measured at two levels of oleic acid. Oral tactile sensitivity was measured using von Frey filaments. Fungiform papillae density (FPD) was measured on the tongue anterior. Mouth behaviour (MB) was measured by Graphic Jeltema/Beckley Mouth Behaviour (JBMB) classification tool. Mouthfeel perception (hardness, crunchiness, and greasiness) in a biscuit model was measured to examine the influence of FPD, tactile sensitivity and MB on mouthfeel perception. Higher FPD was significantly related to higher taste sensitivity to fatty acid and to higher oral tactile sensitivity. FPD and oral tactile sensitivity both significantly influenced mouthfeel perception of biscuits. The results demonstrate the need to characterise individual differences in oral sensory perception by more than one method, and suggest oral tactile sensitivity can be used as a marker of FPD. Further studies are required to understand the impact of MB on sensory perception. The BMI of participants in this study was negatively related to oral tactile sensitivity and the perception of greasiness.